Formulation Process of the Institutional Policy onChildhood and Adolescence (PINA) of the NationalUniversity (UNA) of Costa Rica as a Strategy toPromote the Advancement of the Rights of Minors - Chaverri Chaves, Pablo (2025)
The objective of this article is to systematize the process of formulation and approval of the Institutional Policy for Children and Adolescents (PINA) of the National University (UNA) of Costa Rica during the period 2016-2021. With the implementation of the PINA, it seeks to strengthen the university’s social commitment to minors, the realization of new actions and the deepening of existing ones; this is intended to contribute to them receiving better protection and achieving higher levels of well-being, in accordance with the regulations of the UNA and the Convention on the Rights of the Child, ratified by Costa Rica in 1990. It is based on the theoretical reference provided by the analysis of public policies by Torres-Melo and Santander (2013), which establishes a rational approach to formulation as one of the four stages in the cycle of a public policy. The analysis methodology used was based on the systematization of experiences proposed by Vila (2019), developed in three stages: documentary review, ordering of the information and analysis of the data. The main components of the systematization are: historical trajectory of the PINA, mapping of actors, identification of problems, analysis of objectives, chain of results and framework of indicators at the level of policy effects. The process of formulating the PINA was based on a participatory and multisectoral identification of the problem, which provided valuable inputs and significantly enriched the relevance, orientation, and clarity of its construction.